Genomic differentiation and intercontinental population structure of mosquito vectors Culex pipiens pipiens and Culex pipiens molestus - Yurchenko, Andrey A. (Sci Rep, 2020)
Understanding the population structure and mechanisms of taxa diversification is important for organisms responsible for the transmission of human diseases. Two vectors of West Nile virus, Culex pipiens pipiens and Cx. p. molestus, exhibit epidemiologically important behavioral and physiological differences, but the whole-genome divergence between them was unexplored. The goal of this study is to better understand the level of genomic differentiation and population structures of Cx. p. pipiens and Cx. p. molestus from different continents. We sequenced and compared the whole genomes of 40 individual mosquitoes from two locations in Eurasia and two in North America. Principal Component, ADMIXTURE, and neighbor joining analyses of the nuclear genomes identified two major intercontinental, monophyletic clusters of Cx. p. pipiens and Cx. p. molestus. The level of genomic differentiation between the subspecies was uniform along chromosomes. The ADMIXTURE analysis determined signatures of admixture in Cx. p. pipens populations but not in Cx. p. molestus populations. Comparison of mitochondrial genomes among the specimens showed a paraphyletic origin of the major haplogroups between the subspecies but a monophyletic structure between the continents. Thus, our study identified that Cx. p. molestus and Cx. p. pipiens represent different evolutionary units with monophyletic origin that have undergone incipient ecological speciation.